Handling of Narcotics Crimes Committed by Minors in the Perspective of the Juvenile Criminal Justice System - Melindah Prestianty; Juhriati; Ilham (al-Afkar, Journal For Islamic Studies, 2025)
This study analyzes the handling of child drug cases, specifically the case of AA in Desa Tambe, Bima Regency. While Indonesian regulations emphasize rehabilitation and restorative justice, implementation is hampered by various factors, including inconsistencies in regulations, a lack of training for law enforcement officers, limited rehabilitation facilities, and weak inter-agency coordination. This study, employing a normative juridical method and a statutory approach, finds that a child-centered and restorative approach is crucial. Recommendations include harmonizing regulations, training law enforcement, improving rehabilitation facilities, and strengthening collaboration among agencies and the community to create a system that truly protects and rehabilitates children involved in drug abuse